On the Edge: The Visual Representation of Young Protagonists as Wanderers - Pini, Sara (Linguæ & - Journal of Modern Languages and Cultures, 2023)
The idea of childhood as an innocent life stage, which developed during Romanticism, is still pervasive in the contemporary era and it influences children’s literature. This article provides further evidence for this by focusing on the specific production for young adults. Adolescence has its own characteristics that make it different from childhood: in particular, it is an in-between life stage, projected towards adulthood. Friedrich’s painting Wanderer above the Sea of Fog (1818) provides the visual composition at the basis of recent book covers for Young Adult novels, such as Ian McQue’s artwork for the Scholastic 2018 reissue of the Mortal Engines series (2001-2006) by Philip Reeve. The depiction of young protagonists in the same position as Friedrich’s wanderer shows how adults’ view on adolescence is influenced by the Romantic idea of childhood and, simultaneously, it conveys how adolescents feel attracted by adulthood and on the edge of their childhood.